Right versus left thoracic approach oesophagectomy for oesophageal cancer: a systematic review and meta-analysis protocol. Issue 7 (9th July 2019) - Chai, Tianci; Shen, Zhimin; Chen, Sui; Lin, Yuhan; Zhang, Zhenyang; Lin, Wenwei; Hong, Junjie; Yang, Chuangcai; Kang, Mingqiang; Lin, Jiangbo
Abstract : Introduction: Oesophageal cancer is one of the most common malignant tumours and has been identified as one of the leading causes of cancer death worldwide. Surgery is considered to be the optimal treatment for patients with resectable oesophageal cancer. Oesophagectomy for oesophageal cancer can significantly extend the survival period of patients and provide a potential opportunity for a cure. However, there is still controversy regarding which thoracic approach (right or left) during oesophagectomy for oesophageal cancer can lead to better surgical outcomes globally. This systematic review and meta-analysis will be performed to determine which thoracic approach during oesophagectomy will achieve longer patient survival and will be more beneficial for patients. Methods and analysis: We will search PubMed, Web of Science, Embase, Cancerlit, the Cochrane Central Register of Controlled Trials and Google Scholar databases for relevant clinical trials published in any language before 1 October 2019. Randomised controlled trials (RCTs), quasi-RCTs, propensity score-matched comparative studies and prospective cohort studies of interest, published or unpublished, that meet the inclusion criteria will be included. Subgroup analysis of the type of operation, tumour pathological stage and ethnicity will be performed. PROSPERO registration number: CRD42019124133. Ethics and dissemination: Because this study will be based on published or unpublished records and studies, there is no need for ethics approval. The results of the study will be published in a peer-reviewed journal.